Impact of Roundtable on Sustainable Palm Oil (RSPO) Certification on The Indonesian CPO Exports to The Destination Countries - Fachry Husein Rosyadi; Dwidjono Hadi Darwanto; Jangkung Handoyo Mulyo (Agro Ekonomi, 2020)
Palm oil is one of the plantation commodities that has an important role in economic contribution in Indonesia because of its ability to produce vegetable oil which is essential for industrial sector. The potential development of Indonesia's palm oil exports is high considering the benefits derived from these products. Therefore, there is a need to ensure that CPO products have a sustainable nature, one of which is that CPO products must be RSPO certified. This study analyzes how the influence of various factors that can affect Indonesia's CPO exports, one of which is RSPO certification using panel regression with the basic gravity model. The data which is used in this research is panel data in the form of time series for 20 years with cross sections from five major importing during 1999-2018. The analysis shows that the exchange rate and the RSPO significantly and positively affect Indonesia's CPO exports, while the population of the importing country has a significant and negative effect. This confirms that the presence of RSPO certified products will increase Indonesian CPO exports to major importing countries. Although the RSPO has an effect on Indonesia's CPO exports, there are still a number of indicators from it, in which, Indonesia has not been able to fulfill. That indicator can be used as a material for consideration to be adopted in national certifications such as ISPO so that Indonesian CPO products can be perceived to be sustainable so that they can reach wider export markets.